Cities in the 21st century: a view from the developing world - Castells, David; Herrera, Paula (REGION, 2019)
In this (introductory) paper, we present i) some basic figures about the rise of cities in the developing world, and ii) the four papers of this special issue. This paper and the other four papers in the issue have the intention to bring to the frontline the reality of cities of the developing world in the 21st century, hoping to motivate further and much needed research.